Reflections on the Political Nature within the Teaching Practice: Novelty Teachers' Educational Experiences - Patricia Hermosilla (University of Bologna, 2019)
This research study focuses on the development of teachers' pedagogical knowledge. Its main objective is to comprehend the values, purposes and rationale that lie beneath teaching training programs. Therefore, the focal point of the present study is to examine the experiences that are often found in teaching practices. The methodology of this investigation follows an epistemological and interpretative perspective through the use of a biographical-narrative approach. In this regard, from the analysis of teachers' accounts it is expected to first, reflect on their educational experiences, second, weigh the meaning behind their daily teaching practices and interactions with students, and finally, extend on their experiences as teaching program students. For this purpose, the accounts of two secondary school teachers are portrayed. The findings reveal the complexity of the pedagogical practice as a reflective profession which, in turn, triggers moral, affective and political repercussions (Arnaus, 1999).